The Costa Rican Indigenous Act of 1977: Origins and Negotiations in the 1970s - Boza Villarreal, Alejandra (2025)
This article identifies some of the political and social factors that made it possible for Costa Rica to pass a 1977 law recognizing specific rights for “indigenous communities”. Titled Indigenous Act, it was considered very progressive for its time and it remains in effect to this day. Despite constituting the main legal reference dictating the relationship between the state and the indigenous peoples, no study has been found dedicated to explaining its origin. The research is based on an extensive review of primary sources, including numerous laws and executive decrees, the dossier containing the Indigenous Act’s legislative discussion as well as legislative dossiers from related laws, an interview with one of the main promoters of the Act, and several articles from 1960s and 1970s Costa Rican newspapers. The article argues that the approval of the Indigenous Act was not an isolated event but part of an ongoing legal and political discussion on indigenous rights. This discussion dates back to the late 1930s and, in some respects, even to the colonial period. Two elements advanced the Act’s approval. The significant media attention garnered in the 1970s by the territorial dispossession that indigenous peoples were undergoing constitutes the first element. Continuous reports by indigenous individuals and organizations in alliance with various social sectors fueled such attention. The support that different political parties in Congress provided for both the drafting and the passage of the Act is the second element. Even though indigenous peoples seem to have had little direct input on the Act’s actual language, the document would not have evolved into its final form, and elicited the wide support it did, without the mobilization of indigenous peoples and their allies.